SEISMIC SIGNAL SELECTION USING BACK-PROPAGATED NEURAL NETWORKS - LAZARENKO, M.; HERASYMENKO, O.; OSTAPCHUK, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
Feedforward, multi-layered, supervised network of artificial neurons is backpropagated to be used as classificator to discriminate automatically the seismic data flow into two classes: noise and not noise. The application of the algorithm to 1D seismic records is illustrated.